2018
DOI: 10.1039/c8nr05050c
|View full text |Cite
|
Sign up to set email alerts
|

Cerium(iii)-directed assembly of glutathione-capped gold nanoclusters for sensing and imaging of alkaline phosphatase-mediated hydrolysis of adenosine triphosphate

Abstract: Aggregation-induced emission enhancement (AIEE) of thiolated gold nanoclusters (AuNCs) has emerged as an attractive and alternative strategy to improve their brightness. This study demonstrates Ce(iii)-triggered AIEE of glutathione-capped AuNCs (GSH-AuNCs) through the coordination between two carboxylic groups of GSH and Ce(iii). The cluster size and valence state of GSH-AuNCs are almost identical to those of a Ce(iii)-induced assembly of GSH-AuNCs (named Ce(iii)-GSH-AuNCs). More importantly, the as-prepared C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 48 publications
2
46
0
Order By: Relevance
“…However, the luminescence intensities of the GSH-protected AuNCs obtained under both continuous and intermittent heating modes were weaker ( Figure 2 , traces R2 and R3). The absolute QY for GSH–AuNCs obtained under optimal conditions was determined to be 1.8%, which was similar to the reported values, i.e., 1% [ 40 ], 2% [ 41 , 42 ], and 1.2% [ 11 ]. In contrast, the GSSG–AuNCs possessed significantly higher luminescent efficacy, offering an absolute QY of 4.1%.…”
Section: Resultssupporting
confidence: 87%
“…However, the luminescence intensities of the GSH-protected AuNCs obtained under both continuous and intermittent heating modes were weaker ( Figure 2 , traces R2 and R3). The absolute QY for GSH–AuNCs obtained under optimal conditions was determined to be 1.8%, which was similar to the reported values, i.e., 1% [ 40 ], 2% [ 41 , 42 ], and 1.2% [ 11 ]. In contrast, the GSSG–AuNCs possessed significantly higher luminescent efficacy, offering an absolute QY of 4.1%.…”
Section: Resultssupporting
confidence: 87%
“…You et al. reported that the XPS spectrum of GSH−Au(I) complexes, obtained from the direct mixing of GSH and HAuCl 4 , exhibited a peak corresponding to Au(I) with a binding energy of 84.1 eV . By fitting the Au 4f 7/2 peak of the AuSO spectrum with the same binding energy, the AuSOs were suggested to consist of almost 100 % Au(I) (Figure H).…”
Section: Resultsmentioning
confidence: 98%
“…Among the fluorescent probes, gold nanoclusters (AuNCs) have attracted great attention in biosensing and biomedicine due to its facile synthesis and good biocompatibility. However, the luminous performance of AuNCs is far inferior to those of the developed fluorophores (quantum dots, for instance), and their quantum yield rarely exceeds 0.1% . Therefore, studies have centered on enhancing the performance of AuNCs and explaining the mechanism of their luminescence.…”
Section: Introductionmentioning
confidence: 99%